(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
The identification of biological materials, especially blood traces, and the determination of their species origin are crucial aspects of forensic medical examination and laboratory diagnostics. In contemporary practice, the use of reliable, accurate, and relatively simple methods is essential. The gel diffusion method, particularly the radial immunodiffusion reaction, is based on antigen-antibody interaction and demonstrates high specificity in detecting blood proteins.